Preparation method of modified lithium manganate positive electrode material
Through the preparation method of modified lithium manganese oxide positive electrode material, the problem of deterioration of cyclic performance of lithium manganese oxide positive electrode material under high magnification and high temperature conditions is solved, and the ratiometric and cycle stability of the material is improved, while simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202411489347.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-25
AI Technical Summary
The cycling performance of the existing lithium manganate positive electrode materials deteriorates under high magnification and high temperature conditions, resulting in serious capacity attenuation, complex process and high cost.
The modified lithium manganate positive electrode material was prepared by one low-temperature calcination (pre-fired) and two sintering. First, the lithium source, manganese source and N compound are mixed at high speed and pre-sintered to form a precursor; then the first sintering and annealing are mixed with the T compound to improve the elemental distribution and oxygen defect problems; finally, the second sintering is mixed with the F compound to form a cladding layer to reduce electrolyte erosion.
It effectively reduces the side reactions caused by Mn(III) dissolution and excessive crystal surface activity, improves the rateability and cycle stability of lithium manganese oxide positive electrode material, and simplifies the process and reduces costs.
Smart Images

Figure CN119503885A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing a modified lithium manganate positive electrode material. Background Art
[0002] As a new type of energy storage device, lithium-ion batteries have the advantages of high energy density, long cycle life, no pollution, low self-discharge rate, and no memory effect, and have been widely used in daily life. At present, the industrialized positive electrode materials mainly include lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, ternary nickel cobalt manganese, ternary nickel cobalt aluminum, etc.
[0003] The widespread application of spinel lithium manganese oxide is still limited by severe capacity decay. Its failure mechanism has been discussed in depth and can be summarized as follows: (1) Mn 3+ The disproportionation of Mn 2+ The production of Mn 3 O 4 and the appearance of MnO phase, affecting Li + Transmission; (3) Mn 3+ The Jahn–Teller effect produces a tetragonal Li 2 Mn 2 O 4 This phase is more likely to be produced at high rates, seriously affecting the cycle life.
[0004] Good rate performance means that lithium-ion batteries can maintain high energy output and absorption speed at high rates without losing too much energy or causing battery overheating due to high rates. During the charge and discharge process of lithium-ion batteries, lithium ions are transported through a variety of surfaces and interfaces, among which the properties of the surface and interface of the positive electrode material have an important influence on the battery rate performance. Doping modification and coating materials are effective methods to improve the surface and interface problems of positive electrode materials.
[0005] There are two main methods for surface modification of lithium manganese oxide positive electrodes: (1) wet chemical method. Such as gel sol method, hydrothermal / solvothermal coating. (2) gas phase chemical process. Such as chemical vapor deposition (CVD), atomic layer deposition (ALD). The above methods have the disadvantages of complex process, high cost, uneven thickness of the surface modification layer and uneven distribution of doping elements in the surface modification layer.
[0006] The current surface modification methods for lithium manganese oxide positive electrodes are complex and costly, and are prone to side reactions between highly active crystal planes {110} and {101} and electrolytes, which increase gas production and lead to serious capacity decay. This has led to a continuous deterioration in the cycle performance of lithium manganese oxide, especially the defects in high-temperature performance, which has limited its wide application. Therefore, it is necessary to provide an improved technical solution for the above-mentioned deficiencies in the prior art. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a modified lithium manganate positive electrode material.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a modified lithium manganese oxide positive electrode material comprises the following steps:
[0010] Step 1: Mixing a lithium source, a manganese source and a N compound at high speed to obtain a mixed material; the N compound is one or more of oxides, hydroxides, phosphates and carbonates containing niobium, molybdenum and tungsten;
[0011] Step 2: placing the mixed material in an air atmosphere, pre-calcining it at a temperature of 500-700° C., naturally cooling it to room temperature, crushing it, and sieving it to obtain a precursor;
[0012] Step 3: After the precursor and the T compound are mixed at high speed, they are first sintered at 700-850° C. in an air atmosphere; and the temperature is lowered to 600-750° C., annealed for 2-10 hours, and then crushed and sieved to obtain a modified lithium manganate material; the T compound is one or more oxides of titanium, zirconium, vanadium, aluminum, magnesium, and lanthanum;
[0013] Step 4: Evenly mix the modified lithium manganate material and the F compound, perform a second sintering at 450-600° C., cool, and screen to obtain a finished product of the coated lithium manganate material; the F compound is one or more fluorine-containing compounds other than fluorine-containing acid.
[0014] Furthermore, in step 1, the molar ratio of the lithium source, the manganese source and the N compound is (1.045-1.15):(2-xy):x, wherein 0.01≤x≤0.05, 0.01≤y≤0.05, and y is the molar ratio of the T compound to the precursor.
[0015] Furthermore, in step three, the molar ratio of the precursor to the T compound is 100:(1-3).
[0016] Furthermore, in step 4, the F compound is 0.5%-3% of the mass of the modified lithium manganate material.
[0017] Furthermore, the annealing time is 4-8h, the cooling rate is controlled at 1-5℃ / min and the cooling rate is slower than the heating rate of the first sintering; the first sintering is the main sintering temperature zone, and the annealing cooling rate is slow, which can make the crystal cooling and tempering effect better, and the structure oxygenated and stable.
[0018] Furthermore, the pre-sintering time is 6-10 hours, and the heating rate is 1-10°C / min; the first sintering time is 6-20 hours, and the heating rate is 1-10°C / min; the second sintering time is 2-10 hours, and the heating rate is 1-5°C / min.
[0019] Furthermore, the pre-sintering temperature is 510-550°C, the duration is 6-8h, and the heating rate is 3°C / min; the first sintering temperature is 750-800°C, the duration is 8-10h, and the heating rate is 5°C / min; the annealing temperature is 650-700°C, the duration is 6-8h, and the cooling rate is 2°C / min; the second sintering temperature is 500°C, and the duration is 6-10h.
[0020] Furthermore, in step 2, after crushing, the material is sieved through a 250-mesh sieve, and the material under the sieve is taken to obtain a precursor; in step 3, after crushing, the material is sieved through a 300-mesh sieve, and the material under the sieve is taken to obtain a modified lithium manganese oxide material; in step 4, after the second sintering, the material is sieved through a 300-mesh sieve, and the material under the sieve is taken to obtain a finished product of the coated lithium manganese oxide material.
[0021] The working principle of the present invention is: the present invention uses one low-temperature calcination (pre-burning) + two sinterings to prepare the modified lithium manganese oxide positive electrode material, which generally includes the following steps:
[0022] 1) The lithium / manganese / N compound mixture is calcined at 500-700°C to prepare a precursor; the purpose is to modify the lithium manganate material with the N compound, and doping with transition metal elements can stabilize the oxygen atoms on the crystal surface, reduce oxygen loss during circulation, stabilize the Mn-O structure, and reduce Mn dissolution;
[0023] 2) The precursor is doped with a T compound, and the modified lithium manganate material is obtained by the first sintering (700-850°C) and annealing (600-750°C); the purpose is to improve the element distribution and oxygen defect problems through secondary doping modification, high temperature sintering and high temperature annealing; after doping some elements, it is easier to form a high exposed {111} crystal plane with the minimum surface energy at a suitable temperature, and the Mn atoms on this crystal plane are most closely arranged, which can reduce Mn dissolution;
[0024] 3) The modified lithium manganese oxide material is coated with the F compound, sintered for a second time, and sieved to obtain a finished coated lithium manganese oxide material; the purpose is to reduce the corrosion effect of the electrolyte on the material surface by coating.
[0025] The beneficial effects of the present invention are:
[0026] The preparation method of the present invention reduces the Mn (III) dissolution problem of octahedral spinel morphology materials, and can reduce the probability that the crystal surface activity of truncated spinel morphology materials is too large and side reactions with electrolytes occur easily, resulting in excessive gas production; during the high-temperature annealing process, the bulk doping elements are precipitated and enriched on the surface of lithium manganese oxide to form a uniform surface doping layer, so that the lithium manganese oxide positive electrode material has good rate performance and cycle stability;
[0027] The preparation method of the invention is simple, is carried out in an air atmosphere, and the only heating equipment used is a muffle furnace, which has low cost, short process time, and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0029] Figure 1 This is a scanning electron microscope image of the sample in Example 1.
[0030] Figure 2 This is a scanning electron microscope image of the sample in Comparative Example 1.
[0031] Figure 3 The graph is a cycle performance graph of button batteries assembled from materials prepared in the examples and comparative examples. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0033] A method for preparing a modified lithium manganese oxide positive electrode material comprises the following steps:
[0034] Step 1: Mixing a lithium source, a manganese source and a N compound at high speed to obtain a mixed material; the N compound is one or more of oxides, hydroxides, phosphates and carbonates containing niobium, molybdenum and tungsten;
[0035] Step 2: placing the mixed material in an air atmosphere, pre-calcining at 500-700°C for 6-10h with a pre-calcining heating rate of 1-10°C / min, naturally cooling to room temperature, crushing, and sieving to obtain a precursor;
[0036] Step 3, after the precursor and the T compound are mixed at high speed, the first sintering is performed at 700-850°C in an air atmosphere, the calcination time is 6-20h, and the heating rate is 1-10°C / min; and the temperature is lowered to 600-750°C, annealed for 2-10h, and then crushed and sieved to obtain a modified lithium manganate material; the T compound is one or more oxides of titanium, zirconium, vanadium, aluminum, magnesium, and lanthanum;
[0037] Step 4: Evenly mix the modified lithium manganate material and the F compound, perform a second sintering at 450-600°C, the calcination time is 2-10 hours, and the heating rate is 1-5°C / min; then cool and screen to obtain a finished product of the coated lithium manganate material; the F compound is one or more fluorine-containing compounds other than fluorine-containing acid.
[0038] Furthermore, in step one, the molar ratio of the lithium source, the manganese source and the N compound is (1.045-1.15):(2-xy):x, wherein 0.01≤x≤0.05, 0.01≤y≤0.05, and y is the molar ratio of the T compound to the precursor; in step three, the molar ratio of the precursor to the T compound is 100:(1-3); in step four, the F compound is 0.5%-3% of the mass of the modified lithium manganate material.
[0039] Furthermore, the annealing time is 4-8h, the cooling rate is controlled at 1-5℃ / min and the cooling rate is slower than the heating rate of the first sintering; the first sintering is the main sintering temperature zone, and the annealing cooling rate is slow, which can make the crystal cooling and tempering effect better, and the structure oxygenated and stable.
[0040] Furthermore, the pre-sintering temperature is 510-550°C, the duration is 6-8h, and the heating rate is 3°C / min; the first sintering temperature is 750-800°C, the duration is 8-10h, and the heating rate is 5°C / min; the annealing temperature is 650-700°C, the duration is 6-8h, and the cooling rate is 2°C / min; the second sintering temperature is 500°C, and the duration is 6-10h.
[0041] Further, the N compound is one or more of molybdenum oxide, niobium oxide, tantalum oxide, tungsten oxide, strontium molybdate, zinc molybdate, chromium molybdate, strontium tungstate, zinc tungstate, and chromium tungstate. The T compound is one or more of titanium dioxide, zirconium dioxide, sodium zirconate, aluminum zirconate, aluminum titanate, magnesium oxide, and lanthanum oxide. The F compound is one or more of lithium fluoride, magnesium fluoride, sodium fluoride, and ammonium fluoride.
[0042] The present invention prepares a lithium-rich manganese-based positive electrode material (LMO). Compared with traditional materials such as lithium cobalt oxide and lithium iron phosphate, LMO has higher energy density and lower cost; the conventional practice is to improve its electrochemical performance, stability and cycle life through elements such as Ni and Co. The present invention uses transition metals such as niobium, molybdenum and tungsten for doping, which can stabilize the surface oxygen atoms and change the crystal plane structure to stabilize the structure; the first sintering is doped with titanium, zirconium, vanadium, aluminum, magnesium or lanthanum, and the doped T compound elements are enriched on the surface of the material through annealing; the second sintering is coated with fluorine-containing compounds to reduce the corrosion of the electrolyte. The order of the three calcinations in the present invention is unique. The pre-sintering doping is to reduce the surface energy and stabilize the surface oxygen atoms. The first sintering doping elements are preferably annealed enriched elements to stabilize the surface structure; the third sintering coating is the last step.
[0043] The present invention will be described in detail below with reference to embodiments and comparative examples.
[0044] In the following examples and comparative examples, lithium carbonate, manganese tetraoxide and niobium pentoxide (niobium pentoxide is referred to as niobium oxide) are used as lithium source, manganese source and N compound respectively; titanium dioxide is used as T compound; lithium fluoride is used as F compound; and all chemical raw materials are chemically pure (99.5%) or above. The particle size of each raw material is positively correlated with the particle size of the manganese source, and the crushing / screening particle size of the intermediate product and the finished product is roughly the same as that of the raw material, both of which are 0-60 μm. The specific surface area of the finished product of the coated lithium manganate material prepared in the example is between 0.6 and 0.9.
[0045] The muffle furnace adopts Luoyang Shenjia KL-10T box-type electric furnace, the solid phase high-speed mixer is Zhangjiagang Yongli Machinery, SHR-50A high-speed mixer, and the screening equipment adopts Henan Yufan Machinery YFC-1000 vibrating screen.
[0046] Example 1
[0047] A method for preparing a modified lithium manganese oxide positive electrode material comprises the following steps:
[0048] Step 1, lithium carbonate, manganese tetraoxide, and niobium oxide are weighed according to the molar ratio of lithium, manganese, and niobium elements of 1.045:1.97:0.02, and then put into a solid phase high-speed mixer, and mix at 1000 rpm for 30 minutes to obtain a mixed material;
[0049] Step 2, pre-sintering: the mixed material is placed in a muffle furnace and sintered at 550°C for 8 hours, with a heating rate of 3°C / min, cooled with the furnace, and then sieved with a 250-mesh sieve, and the sieve is taken to obtain a precursor;
[0050] Step 3, first sintering: weigh the precursor and titanium dioxide according to a molar ratio of 100:1, put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain a fired material; put the fired material into a muffle furnace, sinter at a high temperature of 800°C for 8h, and the heating rate is 5°C / min; cool the fired material after the first sintering and anneal it to improve the distribution of doping elements and crystal oxygen defects by annealing; the annealing temperature is 700°C, the annealing time is 6h, and the cooling rate is 2°C / min; cool it with the furnace, then crush it and sieve it with a 300-mesh sieve, take the sieve under the sieve to obtain a modified lithium manganate material;
[0051] Step 4, second sintering (coating): take the modified lithium manganate material and lithium fluoride according to the mass ratio of 100:1 and put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain the coated material; put the coated material into a muffle furnace and sinter it at 500℃ for 6h, cool it with the furnace, and then sieve it with a 300-mesh sieve, take the sieve under the sieve, and obtain the finished product of the coated lithium manganate material. In this embodiment 1, the modified lithium manganate material with a coating amount of 1% is obtained.
[0052] Example 2
[0053] The difference between Example 2 and Example 1 is that the molar ratio of niobium element is different, the sintering temperature of the mixed material and the first-fired material is different, and the annealing temperature is different; the molar ratio of titanium dioxide mixed with the precursor in step 3 is different.
[0054] A method for preparing a modified lithium manganese oxide positive electrode material comprises the following steps:
[0055] Step 1, lithium carbonate, manganese tetraoxide, and niobium oxide are weighed according to the molar ratio of lithium, manganese, and niobium elements of 1.045:1.95:0.03, and then put into a solid phase high-speed mixer, and mix at 1000 rpm for 30 minutes to obtain a mixed material;
[0056] Step 2, pre-sintering: the mixed material is placed in a muffle furnace and sintered at 510°C for 6 hours, with a heating rate of 3°C / min, cooled with the furnace, and then sieved with a 250-mesh sieve, and the sieve is taken to obtain a precursor;
[0057] Step 3, first sintering: weigh the precursor and titanium dioxide according to a molar ratio of 100:2, put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain a fired material; put the fired material into a muffle furnace, sinter at a high temperature of 750°C for 10h, and the heating rate is 5°C / min; cool and anneal the fired material after the first sintering, the annealing temperature is 650°C, the annealing time is 8h, and the cooling rate is 2°C / min; cool and crush with the furnace, and then sieve with a 300-mesh sieve, take the sieve under the sieve to obtain a modified lithium manganate material;
[0058] Step 4, second sintering (coating): take the modified lithium manganate material and lithium fluoride according to the mass ratio of 100:1 and put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain the coated material; put the coated material into a muffle furnace and sinter it at 500℃ for 6h, cool it with the furnace, and then sieve it with a 300-mesh sieve, take the sieve under the sieve, and obtain the finished product of the coated lithium manganate material. In this embodiment 2, the modified lithium manganate material with a coating amount of 1% is obtained.
[0059] Example 3
[0060] The difference between Example 3 and Example 1 is that the reserved amount of titanium dioxide mixed with the precursor in step 3 is different; the sintering and annealing temperature and time of the sintered material are different; and the amount of lithium fluoride used in step 4 is different.
[0061] A method for preparing a modified lithium manganese oxide positive electrode material comprises the following steps:
[0062] Step 1, lithium carbonate, manganese tetraoxide, and niobium oxide are weighed according to the molar ratio of lithium, manganese, and niobium elements of 1.045:1.95:0.02, and then put into a solid phase high-speed mixer, and mix at 1000 rpm for 30 minutes to obtain a mixed material;
[0063] Step 2, pre-sintering: the mixed material is placed in a muffle furnace and sintered at 550°C for 8 hours, with a heating rate of 3°C / min, cooled with the furnace, and then sieved with a 250-mesh sieve, and the sieve is taken to obtain a precursor;
[0064] Step 3, first sintering: weigh the precursor and titanium dioxide according to a molar ratio of 100:3, put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain a fired material; put the fired material into a muffle furnace, sinter at a high temperature of 750°C for 10h, and the heating rate is 5°C / min; cool the fired material after the first sintering and anneal it, and improve the doping element distribution and crystal oxygen defects by annealing; the annealing temperature is 650°C, the annealing time is 8h, and the cooling rate is 2°C / min; cool it with the furnace, then crush it and sieve it with a 300-mesh sieve, take the sieve under the sieve to obtain a modified lithium manganate material;
[0065] Step 4, second sintering (coating): take the modified lithium manganate material and lithium fluoride according to the mass ratio of 100:2 and put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain the coated material; put the coated material into a muffle furnace and sinter it at 500℃ for 8h, cool it with the furnace, and then sieve it with a 300-mesh sieve, take the sieve under, and obtain the finished product of the coated lithium manganate material. In this embodiment 3, the modified lithium manganate material with a coating amount of 2% is obtained.
[0066] The present invention also provides the following comparative example:
[0067] Comparative Example 1
[0068] Comparative Example 1 is a blank group, in which the raw materials are only lithium carbonate and manganese tetraoxide, and the preparation method thereof comprises the following steps:
[0069] Step 1, lithium carbonate and manganese tetraoxide are weighed according to the molar ratio of lithium to manganese element of 1.045:2, and then put into a solid phase high-speed mixer, and mix at 1000 rpm for 30 minutes to obtain a mixed material;
[0070] Step 2: High temperature sintering: The mixed material is placed in a muffle furnace and sintered at 800°C for 8 hours at a heating rate of 3°C / min. The mixed material is cooled in the furnace, crushed, and then sieved with a 250-mesh sieve to obtain Li 1.045 Mn 2 O 4 .
[0071] Comparative Example 2
[0072] Compared with Example 2, the preparation method of this comparative example 2 does not go through the pre-burning step in step 2 and the annealing step in step 3, and the other steps are the same as those of Example 2. The preparation method comprises the following steps:
[0073] Step 1, lithium carbonate, manganese tetraoxide, and niobium oxide are weighed according to the molar ratio of lithium, manganese, and niobium elements of 1.045:1.95:0.03, and then put into a solid phase high-speed mixer, and mix at 1000 rpm for 30 minutes to obtain a mixed material;
[0074] Step 2, first sintering: weigh the mixed material and titanium dioxide according to a molar ratio of 100:2, put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain a fired material; put the fired material into a muffle furnace, sinter at a high temperature of 750°C for 10h, and the heating rate is 5°C / min; cool the fired material after the first sintering and anneal it, and improve the doping element distribution and crystal oxygen defects by annealing; the annealing temperature is 650°C, the annealing time is 8h, and the cooling rate is 2°C / min; cool it with the furnace, then crush it and sieve it with a 300-mesh sieve, take the sieve under the sieve to obtain a modified lithium manganate material;
[0075] Step 3, second sintering (coating): take the modified lithium manganate material and lithium fluoride according to the mass ratio of 100:2 and put them into a solid phase high mixer, mix them at 1000rpm for 30min, and obtain the coated material; put the coated material into a muffle furnace and sinter it at 500℃ for 6h, cool it with the furnace, and then sieve it with a 300-mesh sieve, take the sieve under the sieve, and obtain the annealed coated-not pre-sintered-Li 1.045 Mn 1.95 Nb0.03 Ti 0.02 O 4 .
[0076] Comparative Example 3
[0077] The preparation method of this comparative example 3 does not go through the second sintering (coating) step of step 4, and the other steps are the same as those of Example 3, and finally the pre-sintering-annealing-uncoated-Li 1.045 Mn 1.95 Nb 0.02 Ti 0.03 O 4 The specific steps will not be repeated here.
[0078] Comparative Example 4
[0079] The preparation method of this comparative example 4 does not include the annealing step in step 3, and the other steps are the same as those in Example 3, and finally the pre-sintered coating-unannealed-Li 1.045 Mn 1.95 Nb 0.02 Ti 0.03 O 4 The specific steps will not be repeated here.
[0080] Figure 1 is a scanning electron microscope image of the sample in Example 1, Figure 2 This is a scanning electron microscope image of the sample in Comparative Example 1. Figure 2 It can be seen from the figure that the primary particles of the sample in the comparative example are spinel structures with sharp edges and corners, the material particles have a large specific surface area, and the overall contact area with the electrolyte is large; Figure 1 It can be seen from the figure that after the sample is doped with Nb element, the primary particles are more rounded, the secondary particles are spherical, and the material particles are grown; this indicates that after the doping element of the present invention, the specific surface area of the material particles can be reduced, the contact area with the electrolyte in the battery system can be reduced, and less manganese is dissolved.
[0081] In order to detect the electrochemical performance of the prepared coated lithium manganese oxide material, the lithium manganese oxide positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 were assembled into button cells for electrochemical performance testing.
[0082] The lithium manganate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 were used as active materials, mixed with a binder PVDF and a conductive agent (Super P) in a mass ratio of 90:5:5, and a proper amount of N-vinyl pyrrolidone was added as a solvent to prepare a slurry, which was coated on an aluminum foil, and vacuum dried and rolled to prepare a positive electrode sheet. Metal lithium was used as the negative electrode, and 1 mol / L LiPF 6The electrolyte was formed by mixing a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v), and a polypropylene microporous membrane was used as a separator to assemble a CR2032 button cell in a glove box filled with inert gas. The charge and discharge test of the button cell was carried out at 25°C in a blue battery high temperature charge and discharge test cabinet. The test results are shown in Table 1 below.
[0083] Table 1 Electrochemical properties of button cells obtained in Examples and Comparative Examples
[0084]
[0085] Comparing Example 1 with Example 2, the main difference is that the total doping amount changes from 0.02 (niobium) + 0.01 (titanium dioxide) to 0.03 (niobium) + 0.02 (titanium dioxide), which is mainly the embodiment of the total doping value and when the doping Nb ratio is high, the material can exert a higher gram capacity. Comprehensively comparing Examples 1-3, Example 2 is the best example.
[0086] By comparing Examples 1-3 with Comparative Example 1, it can be clearly seen that the cycle performance of the lithium manganate material in the blank control group is only 92.61% (Comparative Example 1) at 25°C test conditions, and the capacity retention rate of 1C cycle 100 weeks is only 97.5%. The cycle performance of the lithium manganate material of Examples 1-3 is improved to more than 97.5%. This shows that the lithium manganate material is modified by the N compound of the present invention to change the crystal morphology; after secondary doping modification, high temperature sintering and high temperature annealing improve the element distribution and oxygen defect problems; the electrolyte erosion is reduced by coating, and the dissolution of Mn in the electrolyte is greatly reduced, which greatly improves the cycle performance of the lithium manganate positive electrode material.
[0087] Comparing Example 2 with Comparative Example 2, under the same raw material composition, Comparative Example 2 was not pre-burned, and its discharge specific capacity and cycle performance decreased, indicating that low-temperature pre-burning can improve the crystal structure of the material in the first heating process of solid-phase sintering, and improve the cycle and capacity. Without pre-burning, firstly, the temperature is directly raised from low temperature to high temperature, and the lithium volatilization amount will be high during the high temperature process; the crystal growth does not have a stable temperature under the premise of continuous heating, the crystal size is uneven, and the material performance is slightly poor.
[0088] By comparing Example 2, Example 3 and Comparative Example 3, it can be clearly seen that the amount of coating layer will affect the gram capacity (discharge specific capacity) of the material. The more coating, the lower the capacity. Therefore, the recommended coating amount of the fluorine-containing compound is 1%.
[0089] Comparing Example 3 with Comparative Example 4, under the same raw material composition, Comparative Example 4 has not been annealed, and its discharge specific capacity is slightly higher and the capacity retention rate is slightly lower, indicating that the annealing process can improve the crystal surface structure, stabilize crystal growth and crystal surface oxygenation, and enhance the cycle performance of the material.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A method for preparing a modified lithium manganese oxide positive electrode material, characterized in that: The following steps are involved: Step 1: Mixing the lithium source, the manganese source and the N compound at high speed to obtain a mixed material; the N compound is one or more of oxides, hydroxides, phosphates and carbonates containing niobium, molybdenum and tungsten; Step 2: placing the mixed material in an air atmosphere, pre-calcining it at a temperature of 500-700° C., naturally cooling it to room temperature, crushing it, and sieving it to obtain a precursor; Step 3: After the precursor and the T compound are mixed at high speed, the mixture is first sintered at 700-850° C. in an air atmosphere; the mixture is cooled to 600-750° C., annealed for 2-10 hours, and then crushed and sieved to obtain a modified lithium manganate material; The T compound is one or more oxides of titanium, zirconium, vanadium, aluminum, magnesium, and lanthanum; Step 4: Evenly mix the modified lithium manganate material and the F compound, perform a second sintering at 450-600° C., cool, and screen to obtain a finished product of the coated lithium manganate material; the F compound is one or more fluorine-containing compounds other than fluorine-containing acid.
2. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: In step 1, the molar ratio of the lithium source, the manganese source and the N compound is (1.045-1.15):(2-xy):x, wherein 0.01≤x≤0.05, 0.01≤y≤0.05, and y is the molar ratio of the T compound to the precursor.
3. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: In step 3, the molar ratio of the precursor to the T compound is 100:(1-3).
4. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: In step 4, the F compound is 0.5%-3% of the mass of the modified lithium manganate material.
5. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: The annealing time is 4-8h, the cooling rate is controlled at 1-5℃ / min and the cooling rate is slower than the heating rate of the first sintering.
6. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: The pre-sintering time is 6-10 hours, and the heating rate is 1-10°C / min; the first sintering time is 6-20 hours, and the heating rate is 1-10°C / min; the second sintering time is 2-10 hours, and the heating rate is 1-5°C / min.
7. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: The pre-sintering temperature is 510-550℃, the duration is 6-8h, and the heating rate is 3℃ / min; the first sintering temperature is 750-800℃, the duration is 8-10h, and the heating rate is 5℃ / min; the annealing temperature is 650-700℃, the duration is 6-8h, and the cooling rate is 2℃ / min; the second sintering temperature is 500℃, and the duration is 6-10h.
8. The method for preparing the modified lithium manganate positive electrode material according to claim 1, characterized in that: In step 2, after crushing, the material is sieved through a 250-mesh sieve, and the material under the sieve is taken to obtain a precursor; in step 3, after crushing, the material is sieved through a 300-mesh sieve, and the material under the sieve is taken to obtain a modified lithium manganese oxide material; in step 4, after the second sintering, the material is sieved through a 300-mesh sieve, and the material under the sieve is taken to obtain a finished product of the coated lithium manganese oxide material.
Citation Information
Cited By
High-voltage single-crystal lithium manganate, preparation method and application of high-voltage single-crystal lithium manganate
CN120608316A